Optimalisasi Waktu Tunggu dan Alur Pelayanan Obat Rawat Jalan di RSI Nu Demak dengan Pendekatan Lean Hospital - Annisa Nila Agustin Agustin; Ria Etikasari; Ahmad Suriyadi Muslim (KOLONI, 2026)
The development of the hospital sector demands fast, efficient, and high-quality healthcare services, including pharmaceutical services. Waiting time for medication is an important indicator in assessing the quality of outpatient pharmacy services. This study aims to analyze waiting time for medication services, identify waste based on the Lean Hospital concept, and evaluate service flows to improve pharmacy service efficiency. This study used an observational method with a quantitative descriptive approach and was conducted in January 2026. The study sample consisted of 100 outpatient prescriptions determined using the Slovin formula and 23 pharmacists selected using a total sampling technique. Data collection was carried out through direct observation, questionnaires as primary data, and secondary data from the hospital information system (Hosmis). Data analysis was conducted using univariate and descriptive methods. The results showed that outpatient drug services were dominated by non-compounded prescriptions. Waiting times for both non-compounded and compounded prescriptions were still within the standard limits set by Regulation of the Minister of Health of the Republic of Indonesia Number 30 of 2022 concerning National Indicators of Health Service Quality. The implementation of Lean Hospital showed that most aspects, such as motion, inventory, and service flow, were running well. However, waste was still found in transportation, waiting, and overprocessing. The medication service flow was considered clear, structured, and supported service efficiency. The conclusion of this study is that the implementation of Lean Hospital in the outpatient pharmacy installation has been running quite well but not optimally. Improvements are needed, especially in reducing waste and improving coordination between staff to improve service efficiency and optimize the quality of pharmaceutical services.